NAVIGATING THE GLOBAL CHALLENGE OF DIABETES MELLITUS: INSIGHTS FROM KAZAKHSTAN'S HEALTHCARE LANDSCAPE AND STRATEGIES FOR IMPROVED MANAGEMENT - Asselkhan Otegenova; Assem Kazbekova; Maksut Kulzhanov; Zhanay Akanov (Interdisciplinary Approaches to Medicine)
The global prevalence of diabetes mellitus presents a significant challenge to public health, with projections indicating a substantial rise in cases, particularly in low- and middle-income countries. This study acknowledges the critical lack of comprehensive research and under-reporting of diabetes cases, emphasizing the need for improved screening strategies and healthcare access. Theoretical and practical significance is evident in the complexity of estimating prevalence, regional variations in Central Asia, and global initiatives recognizing diabetes as a major health concern. While successful management programs exist, challenges persist, including under-reporting, discrepancies in estimations, and delayed diagnoses, impacting patient quality of life and healthcare costs. Multidisciplinary approaches are essential due to the presence of multiple comorbidities among patients, emphasizing the need for coordinated efforts. Robust data sources and proactive healthcare policies are crucial in understanding prevalence trends and addressing this burgeoning health crisis on a global scale. This study aims to utilize administrative healthcare data from Kazakhstan to comprehensively explore diabetes epidemiology, including demographic factors, mortality, and comorbidities. Findings seek to inform targeted interventions and advance diabetes management strategies within the country's healthcare landscape. The uneven distribution of type 2 diabetes prevalence, particularly among women, underscores the economic and societal significance of the issue, necessitating specialized medical care and focused research efforts. Identifying the true prevalence of diabetes is crucial for planning health improvement, treatment, and preventive measures. Collaboration among specialists is imperative to improve the health outcomes of type 2 diabetes patients, emphasizing the importance of screening and managing chronic non-communicable diseases to mitigate the medical and social impact of this global problem.